1988
DOI: 10.1039/f19888403501
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectra of defective nickel oxide

Abstract: Cation-deficient nickel oxides have been investigated by X-ray photoelectron spectroscopy. The high-binding-energy features in the O( 1 s), Ni(2p) X.P.S. of defective NiO are described as multielectron final states, induced by defective sites. These sites are described as (Ni0,)9-molecular clusters because of the d hole. The energy shift between the main peak and the satellite, in both the O(1s) and Ni(2p) X.P.S. spectra, is due to a change in the ionic charge and in the oxygen coordination induced by cation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 5 publications
3
52
0
Order By: Relevance
“…Finally, it may be concluded that even after surface cleaning and high temperature dehydration the intensity of the peak at ∼531 eV remains comparable with the O 2− -anion peak intensity. This lateral peak may be attributed to low coordinated oxygen [13] and/or to oxygen-deficient regions [22] in the LNO matrix. Unfortunately, the (1), after subsequent Ar + polishing (2), after subsequent super high vacuum annealing (550 • C; 30 h) (3), after subsequent exposure to ambient air for 2 hours (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it may be concluded that even after surface cleaning and high temperature dehydration the intensity of the peak at ∼531 eV remains comparable with the O 2− -anion peak intensity. This lateral peak may be attributed to low coordinated oxygen [13] and/or to oxygen-deficient regions [22] in the LNO matrix. Unfortunately, the (1), after subsequent Ar + polishing (2), after subsequent super high vacuum annealing (550 • C; 30 h) (3), after subsequent exposure to ambient air for 2 hours (4).…”
Section: Resultsmentioning
confidence: 99%
“…The assumption of different valence states for the metal [12] or several final states [13] has been made, but in most cases this structure has been assigned to contamination surface species. The adsorption of (OH) − or CO Jimenez et al [14] attribute the lateral peak to low coordinated oxygen ions at the surface of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Conventionally P 3 Ni is considered to arise from contribution of trivalent nickel species ͑Ni 3+ , excited 3d states 34,35 having 3d 7 electron configuration͒ due to the deficient nickel oxide. 31,[36][37][38] But it can be assigned to Ni͑OH͒ 2 as well as in Refs. 39 and 40.…”
Section: Pure Nickelmentioning
confidence: 99%
“…These high-binding-energy peaks are frequently attributed to Ni 3C species. 36,37 The assignments for the Ni 2p 3/2 feature in bulk Ni 2 O 3 in the literature vary and are reported at 855.1, 855.8 eV, 856.5 and 857.3 eV. 38 -41 The assignment for the bulk Ni 2p 3/2 feature in -NiOOH in the literature is at 855.3 eV.…”
Section: Resultsmentioning
confidence: 97%